Some Consideratıons on The Concepts of Precedent, Constant Jurisprudence and Jurisprudence in Administrative Jurisdiction - Necip Taha Gür (İstanbul Hukuk Mecmuası)
In this study, court decisions are classified in terms of procedural law and examined in the context of the effect of a court decision on other court decisions. After revealing that not all court decisions have the characteristics of jurisprudence, the court decisions that are taken into consideration in order to ensure similar decisions in precedent cases and therefore non-binding court decisions are evaluated. In this respect, the persuasive power of precedent case law as a requirement of legal stability has been revealed. The value of precedent as a source of law is explained by pointing out the differences between Continental European Law and Common Law. The concept of precedent, i.e., the precedent of a case law that has stabilised as well as containing a principle, is discussed within the framework of jurisprudence constant, which is a theory of Continental European jurisprudence. The doctrine of jurisprudence constant, which is accepted as the Continental European equivalent of the doctrine of stare decisis (precedent decision) in common law, has been examined within the framework of both an institution and the concept of peremptory precedent as seen in the decisions of the Council of State. Again, the deviation of the court from the case law in administrative jurisdiction is analysed in the context of the prohibition of surprise decisions. The connection of the unification of jurisprudence, which is an institution specific to Turkish procedural law, with the case law is evaluated considering judicial decisions.